RESEARCH ACTIVITY ANTISEPTICS DECAMETHOXIN MIRAMISTIN AND IN DIFFERENT PHYSICOCHEMICAL CONDITIONS (PH, MICROBIAL LOAD) - Стукан, О.К. (World of Medicine and Biology, 2015)
Research of activity of antiseptic preparations of decametoxine, miramistin in different physical and chemical terms (рн environments, microbal loading). The least concentration of reparation, that detains the by sight certain height of microbes after the corresponding process of incubation, was considered a minimal inhibiting concentration (МIC). The least of preparation, that caused death of microorganisms through set time, was named a minimal bactericidal concentration (МBC). The results of research of antimicrobial activity of decametoxinum on the clinical stamms of staphylococcus showed the following: MIC equaled 0,75±0,06 mcg/ml, MBC grew to 1,50±0,06 mcg/ml. For the clinical stamms of collibacillus MIC decametoxinum equaled 4,48±0,98 mcg/ml, MBC 8,97±2,97 mcg/ml. For stamms miramastinum hesitated a staphylococcus MIC within the limits of 2,47±0,02 mcg/ml, mean value of MBC equaled 4,97±0,66 mcg/ml; stamms of collibacillus were sensible to МР at MIC 9,16±2,9 mcg/ml, MBC folded 18,3±3,72. Studies of unfavorable terms, that can influence on antimicrobial properties of antiseptics, gives an opportunity to use the got information for implementation of practical tasks. The reaction of environment, in that there are microorganisms, presence of albuminous substances, has an important value at a disinfestation. Antimicrobial activity of preparations in the conditions of different concentration of hydrions was determined on environments from рН 7,2; 6,0; 8,0. In parallel studied control of height of cultures of tests on these environments without addition to preparation. In a alkaline environment the bactericidal concentrations of decametoxinum operated on stamms to the staphylococcus within the limits of 7,8±3,43 mcg/ml, the multipleness of change of activity of preparation to control presented 2,1 times. In a alkaline environment MBC decametoxinum folded 4,73±1,42 mcg/ml, and the multipleness of change of activity of preparation equaled 1,7 times. Miramastinum showed next results: MBC at рН 6,0 folded 15,21±3,70 mcg/ml, the multipleness of change of activity of preparation to control presented 2,7 times; MBC at рН 8,0 folded 12,2±3,94. MBC ДКМ in relation to clinical stamms with the microbal loading 10³ КУО/of ml equaled a 4,56±0,93мкг/ml, while loading in 106 КУО/of ml of MBC decametoxinum equaled 4,69±1,6 mcg/ml. MBC decametoxinum with the microbal loading in 109 КУО/of ml folded 9,57±3,96 mcg/ml. Miramastinum showed next results: at the increase of sowing dose of microorganisms to 103 КУО/of ml of MBC of preparation equaled 12,7±3,6 mcg/ml. MBC with loading in 106 КУО/of ml equaled 12,7±3,6 mcg/ml, MBC miramastinum at loading in 109 КУО/of ml grew to 59,65±20,1 mcg/ml.ConclusionsThe investigated antiseptic preparations of декаметоксин and мірамістин have a wide spectrum of antimicrobial action in relation to the causative agents of hospital infections, kept high antimicrobial activity, quickly render harmless.
Keywords: antiseptic preparations; antimicrobial activity; clinical stamms; microbal loading; festering-septic complications